Artificial cell membrane platforms by solvent-assisted lipid bilayer (SALB) formation - Tae, Hyunhyuk (2023)
ConspectusSupported lipid bilayers (SLBs) are artificial cell membrane platforms that recapitulate key aspects of lipid membrane architecture on material surfaces. Their compatibility with a variety of surface-sensitive biophysical techniques highlights the importance of designing and constructing SLBs on target materials. Moreover, the functionalization of SLBs by modulating the lipid compositions and/or incorporating biomolecules provides versatile opportunities to improve understanding of membrane properties and molecular interaction as well as the applications to analytic platforms and diagnostic biosensing. To date, the most favored approach to form SLBs is vesicle fusion, which involves vesicle adsorption and simultaneous rupture on a solid surface. However, this technique is highly dependent on the vesicle preparation, lipid compositions, and types of surface materials. Within this context, there have been tremendous efforts to advance fabrication technology surpassing vesicle fusion, which has led to the development of next-generation SLB platforms and opened the door to a wide range of new applications such as diagnostic biosensors, biocompatible coatings, and bioanalytical tools.In this Account, we summarize recent progress in the innovative SLB fabrication technique termed the solvent-assisted lipid bilayer (SALB) method, which our group has successfully developed to transcend the conventional vesicle fusion method. We particularly focus on the material aspects of the biomimetic SLB platform, including solid substrates and lipid compositions, which can be extended by SALB method. Along with the principles of lipid molecular self-assembly, we first introduce the development of SALB method and compelling advantages of this strategy that integrates simple sample preparation, affinity with a wide range of material supports, and various lipid compositions by comparing with vesicle fusion method. We systematically describe how this approach can be effectively employed to extensive solid substrates and broad lipid compositions via combination of theoretical simulation modeling and experimental analysis by cutting-edge surface-sensitive characterization techniques that have been utilized in our group for the biointerfacial analysis, involving fluorescence microscopy and quartz crystal microbalance with dissipation monitoring (QCM-D). We then critically discuss important exploratory parameters for solvent-assisted lipid self-assembly underpinning this strategy including flow rate, lipid concentrations, types of organic solvent, and temperature to improve fundamental understanding and optimize quantitative conditions. Finally, we present recent application examples encompassing biocompatible antifouling coating, biomolecular interaction monitoring, and extracellular matrix remodeling. With the ongoing development and application of the SALB method, there is a future opportunity to enrich our fundamental understanding of biointerfacial science and lead to new technological breakthroughs and application possibilities of artificial cell membrane platforms for material innovation.